Anti-plant Defense Response Strategies Mediated by the Secondary Symbiont Hamiltonella defensa in the Wheat Aphid Sitobion miscanthi - Li, Qian; Fan, Jia; Sun, JingXuan; Zhang, Yong; Hou, MaoLin; Chen, JuLian (Frontiers in Microbiology, 2019)
Bacterial symbionts are omnipresent in insects, particularly aphids, and often exert important effects on the host ecology; however, examples of symbionts that mediate herbivore-plant interactions remain limited. Here, three clones with identical genetic backgrounds were established: Hamiltonella defensa free clone, H. defensa infected clone and H. defensa cured clone. H. defensa infection was found to increase the fitness of S. miscanthi, which increased the total number of offspring and decreased the age of first reproduction. Furthermore, gene expression studies and phytohormone measurement showed that feeding by the Hamiltonella-infected clone suppressed the salicylic acid (SA)- and jasmonic acid (JA)-related defense pathways and accumulation in wheat plants relative to feeding by the other two clones. Additionally, after feeding by the Hamiltonella-infected clone, the activity levels of the defense-related enzymes polyphenol oxidase (PPO) and peroxidase (POD) in wheat plants were significantly decreased compared with the levels observed after feeding by the other two clones. Taken together, these data reveal for the first time the potential role of H. defensa of S. miscanthi in mediating the anti-plant defense responses of aphids.